2018
DOI: 10.1038/s41433-018-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in childhood blindness and ocular morbidity in India: the Pavagada Pediatric Eye Disease Study 2

Abstract: A major proportion of the blindness was due to unavoidable causes. Unlike several earlier studies, corneal blindness is no longer the main cause of blindness. This shows that there is a changing trend in the pattern of childhood blindness in India. The current data demonstrate the need for low vision rehabilitative services and a review of public health strategy in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Eight thousand five hundred and fifty-three children were examined. The prevalence of ocular morbidity was 6.54% (CI, 6.01-7.06) and blindness was 0.09% (CI, 0.03-0.16) (Kemmanu et al 2018). The prevalence of diseases with a potential genetic etiology was 0.41% (CI, 0.29-0.57).…”
Section: Resultsmentioning
confidence: 98%
“…Eight thousand five hundred and fifty-three children were examined. The prevalence of ocular morbidity was 6.54% (CI, 6.01-7.06) and blindness was 0.09% (CI, 0.03-0.16) (Kemmanu et al 2018). The prevalence of diseases with a potential genetic etiology was 0.41% (CI, 0.29-0.57).…”
Section: Resultsmentioning
confidence: 98%
“…There is a definite change in the pattern of childhood blindness in India; the shift has been from cornea (preventable) as the main cause of blindness to unavoidable causes like whole globe anomalies and retinal pathologies. [ 1 ] This could be because of the vitamin A supplementation program initiated by the Government of India which has led to a decrease in vitamin A deficiency disorders, particularly blindness. [ 2 ] Population-based studies are the gold standard for obtaining data on the prevalence, distribution, and determinants of blindness which would help in setting up appropriate health care delivery.…”
mentioning
confidence: 99%
“…In addition, UNICEF supported the measles–rubella vaccination for approximately 550, 000 children in response to the Yangon measles outbreak. Other recent childhood blindness studies performed in Asia have also found whole globe anomalies to be the main cause of blindness including India (25%),[ 9 ] Lao (30.4%),[ 10 ] and Bhutan (20%). [ 10 ] Corneal opacities, however, still remains the most common site of abnormality in sub-Saharan Africa and areas of extreme deprivation.…”
Section: Discussionmentioning
confidence: 99%